The Transformation of the Role of Islamic Education Teachers in the Era of Artificial Intelligence: Pedagogical Dynamics and Ethical Challenges - Vaya Nyla (Sustainable, 2026)
The development of Artificial Intelligence (AI) has changed students’ learning patterns, including in Islamic Religious Education (PAI). Many students increasingly use AI applications to obtain quick answers, creating new challenges for teachers. While previous studies have largely focused on the effectiveness of AI and digital learning innovations, research examining the changing role of PAI teachers in addressing pedagogical and ethical issues remains limited. Therefore, this study aims to analyze the dynamics of PAI teachers’ roles in the AI era. This study employed a descriptive qualitative approach involving two PAI teachers and 60 students at a public junior high school in Surabaya, selected through purposive sampling. Data were collected through interviews, observations, and documentation. The findings show that AI use encourages a more pragmatic learning pattern among some students, particularly in seeking instant answers without adequate understanding. As a result, the role of PAI teachers has shifted from being the main source of knowledge to becoming facilitators and ethical guides who help students critically evaluate AI-generated information and ensure its alignment with Islamic values. Teachers also face challenges related to students’ declining critical thinking skills and differences in digital competence between teachers and students. This study concludes that the integration of AI requires PAI teachers to reposition their pedagogical and ethical roles. Strengthening digital literacy and Islamic ethical values is essential to ensure that AI is used responsibly and supports meaningful learning.